2011
DOI: 10.2478/s13531-011-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Strength and dynamic characteristics analyses of wound composite axial impeller

Abstract: A low cost, light weight, high performance composite material turbomachinery impeller with a uniquely designed blade patterns is analyzed. Such impellers can economically enable refrigeration plants to use water as a refrigerant (R718). A strength and dynamic characteristics analyses procedure is developed to assess the maximum stresses and natural frequencies of these wound composite axial impellers under operating loading conditions. Numerical simulation using FEM for two-dimensional and three-dimensional im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Thus, though the interfacial bond may be poor, the interface could transfer load more effectively, resulting in the enhancement of their hardness. [11][12][13] The effect of water absorption on the tensile strength of CF/EPDM composites with PA6 fiber loadings at 20 C for melt mixed for different periods of time is depicted in Figure 4. It was found that at all fiber loadings, the composite tensile strength decreased with increase in immersion time.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, though the interfacial bond may be poor, the interface could transfer load more effectively, resulting in the enhancement of their hardness. [11][12][13] The effect of water absorption on the tensile strength of CF/EPDM composites with PA6 fiber loadings at 20 C for melt mixed for different periods of time is depicted in Figure 4. It was found that at all fiber loadings, the composite tensile strength decreased with increase in immersion time.…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the mesh density step by step, a suitable number of elements are obtained. 39 There are totally 75,132 nodes and 77,256 elements generated by dividing the composite rotor along its radial and circumferential direction. Because of the orthotropic properties of the composite material, cylinder element coordinate system is set in the FE model.…”
Section: Stresses and Displacements Caused By Centrifugal Loadsmentioning
confidence: 99%
“…Tzeng and Moy 37 designed a composite energy storage flywheel for fatigue crack resistance. Wang et al 38,39 researched the stress and dynamic characteristics of the wound composite material axial impeller under centrifugal force loading conditions based on finite element analysis. By addition of resin acceptor to improve the interface state between fiber and matrix of resin or by modification of epoxide resin to improve the radial strength of the solidified resin to some extent, some regarded the radial structure of composite rotor as cascade model with fiber, interface and matrix to find methods to increase the SED but these methods cannot improve the radial strength of the monodirectional composite material greatly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations